Software technologies : 10th International Joint Conference, ICSOFT 2015, Colmar, France, July 20-22, 2015, Revised selected papers /: 10th International Joint Conference, ICSOFT 2015, Colmar, France, July 20-22, 2015, Revised selected papers. (2016) - Unknown
No abstract available